2022
DOI: 10.1111/cup.14340
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, pathological, and molecular correlation of folliculocystic and collagen hamartoma: A new potential diagnostic criterion for tuberous sclerosis complex?

Abstract: Folliculocystic and collagen hamartoma (FCCH) is a rare entity with only 18 reported cases worldwide. Of them, most are found in patients diagnosed with tuberous sclerosis complex (TSC). FCCH has distinctive histopathologic features, including collagen deposition in the dermis, perifollicular fibrosis, and comedones with keratincontaining cysts lined by infundibular epithelium. We report three patients with a definitive TSC clinical diagnosis in whom clinical, histopathologic, and molecular features were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…FCPs and FCCHs share some histopathologic features, such as collagen deposits, capillary dilation, and concentric fibrosis around follicles. However, FCCHs are also characterized by dilatation of the infundibular portion of the follicle and the presence of comedo-like openings [6]. Histopathologic evaluation of the present patient indicated that the large and bulky lesions were diagnostic of FCPs.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…FCPs and FCCHs share some histopathologic features, such as collagen deposits, capillary dilation, and concentric fibrosis around follicles. However, FCCHs are also characterized by dilatation of the infundibular portion of the follicle and the presence of comedo-like openings [6]. Histopathologic evaluation of the present patient indicated that the large and bulky lesions were diagnostic of FCPs.…”
Section: Discussionmentioning
confidence: 50%
“…Skin biopsies showed normal epidermis with abundant collagen fibers forming nodules surrounding the gland ducts, hair follicles, and vessels in the deep dermis. These findings were compatible with FCP, as no follicular comedo-like openings or follicularsebaceous cystic dilations were present [4,6].…”
Section: Genetic Analysesmentioning
confidence: 55%
See 1 more Smart Citation
“…The prevailing theory suggests the involvement of TSC1/TSC2 genes and sex hormones in its pathogenesis, yet the emergence of cases in females and those without tuberous sclerosis contradicts this hypothesis [ 5 ]. A case series studying patients with FCCH in tuberous sclerosis patients identified heterozygous pathogenic variants in the TSC2 gene in tumor tissue samples, without evidence of a TSC2 second hit, suggesting a potential genotype-phenotype correlation [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proposed as an atypical variant of collagen hamartoma, FCCH demonstrates unique histopathological and clinical features [ 1 ]. The disease typically presents as an exophytic plaque with an elastotic consistency and comedo-like openings, with over half of the cases appearing in infancy or early childhood [ 2 ]. The head is the most common site of involvement, with genital involvement never previously reported.…”
Section: Introductionmentioning
confidence: 99%